Quality of life and its determinants in people living with human immunodeficiency virus infection in Puducherry, India - T Mahalakshmy; K C Premarajan; Abdoul Hamide (Wolters Kluwer Medknow Publications, 2011)
Context: With anti-retroviral therapy (ART) for human immunodeficiency virus infection (HIV) coming into picture, quality of life (QOL) has gained importance. Knowledge on the factors affecting QOL would be helpful in making important policy decisions and health care interventions. Aims: The aim of this study is to assess the quality of life of people living with HIV (PLWH) and to identify the factors influencing their QOL. Materials and Methods: The study was done among 200 PLWH attending a tertiary care hospital, and three Non Governmental Organizations at Puducherry, India, from November 2005 to May 2007. QOL was assessed using HIV specific World Health Organization Quality Of Life scale (WHOQOL-HIV) - BREF questionnaire which has six domains (physical, psychological, level of independence, social relationships, environment and spirituality/religiousness/personal belief). Social support and stigma were measured using "Multidimensional Scale of Perceived Social Support" and "HIV Stigma Scale," respectively, using Likert Scale. Factors influencing QOL were identified using backward stepwise multiple linear regression with the six domain scores as the dependent variables. Results: Male: Female ratio was 1:1 and 58% were in early stage of the disease (stage I/II). Psychological and SRPB (Spirituality Religiousness and Personal Beliefs) domains were the most affected domains. All the regression models were statistically significant (P<0.05). The determination coefficient was highest for the social relationship domain (57%) followed by the psychological domain (51%). Disease stage and perceived social support significantly influenced all the domains of WHOQOL. Younger age, female gender, rural background, shorter duration of HIV, non-intake of ART and greater HIV related stigma were the high risk factors of poor QOL. Conclusion: Interventions such as ART, family, vocational and peer counseling would address these modifiable factors influencing QOL, thereby improving the QOL of PLWH.